Integration of Photovoltaic Shading Device and Vertical Farming on School Buildings to Improving Indoor Daylight, Thermal Comfort and Energy Performance in Three Different Cities in China - Weihao Hao; Jiahua Xu; Feiyu Zhao; Dong-Wook Sohn; Xuepeng Shi (Buildings)
This study explores the integration of photovoltaic (PV) shading devices and vertical farming (VF) in school buildings to optimize indoor daylight, thermal comfort, and energy performance across three different climate regions in China: Beijing, Shanghai, and Shenzhen. With rapid urbanization and increasing energy consumption in educational buildings, this research investigates the impact of innovative facade design on both energy efficiency and occupant comfort. Through parametric simulations and multi-objective optimization, various PV and VF facade prototypes were evaluated to determine the best configurations for reducing energy consumption while enhancing thermal and visual comfort. This study optimized facade systems integrating photovoltaic and vertical farming for school buildings in Shenzhen, Beijing, and Shanghai. Key findings include: In Shenzhen, Model B’s UDI increased by 5.1% and Model C by 19.02%, with glare areas reduced by 5.4% and 21.40% and stable thermal comfort (PMV 0.52–0.59) throughout the year. In Beijing, Model B’s UDI decreased by 0.2%, while Model C increased by 6.55%. Glare areas reduced by 2.92% and 14.35%, with improved winter comfort (PMV −0.35 to −0.1). In Shanghai, Model C’s UDI increased by 6.7%, but summer thermal discomfort was notable (PMV up to 1.2). The study finds that PV shading systems combined with vertical farming can provide significant energy savings, reduce greenhouse gas emissions, and offer organic vegetable production within school environments. The findings suggest that integrating these systems into the building envelope can optimize the energy performance of school buildings while improving the comfort and well-being of students and staff.